(untitled) (TAMADDUN NURI JURNALI, 2024)
This article describes some aspects of the formation of aesthetic upbringing in the Uzbek mahalla. The role of aesthetic upbringing the upbringing of the younger generation and the factors of its formation are analyzed aesthetically.